2012
DOI: 10.1021/jf3002125
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Saponins in Quinoa Samples (Chenopodium quinoa Willd.) Grown under Different Saline and Nonsaline Irrigation Regimens

Abstract: Quinoa is a pseudocereal from South America that has received increased interest around the world because it is a good source of different nutrients and rich in antioxidant compounds. Thus, this study has focused on the effects of different agronomic variables, such as irrigation and salinity, on the phenolic and saponin profiles of quinoa. It was observed that irrigation with 25% of full water restitution, with and without the addition of salt, was associated with increases in free phenolic compounds of 23.16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 42 publications
11
96
2
1
Order By: Relevance
“…Hydroxybenzoic and hydroxycinnamic free forms and derivatives have been previously described in different quinoa varieties by other authors (Alvarez‐Jubete et al ., ; Repo‐Carrasco‐Valencia et al ., ; Gómez‐Caravaca et al ., , ; Carciochi et al ., ). These authors identified vanillic glucoside and feruloyl glucoside as hydroxybenzoic and hydroxycinnamic acids, vanillic, p ‐coumaric and ferulic acids as bound acids and flavonols such as kaempferol and quercetin 3‐ O ‐apifuranosyl‐galactopyranoside, kaempferol and quercetin 3‐ O ‐dirhamnosyl‐galactopyranoside, quercetin glucuronide and others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxybenzoic and hydroxycinnamic free forms and derivatives have been previously described in different quinoa varieties by other authors (Alvarez‐Jubete et al ., ; Repo‐Carrasco‐Valencia et al ., ; Gómez‐Caravaca et al ., , ; Carciochi et al ., ). These authors identified vanillic glucoside and feruloyl glucoside as hydroxybenzoic and hydroxycinnamic acids, vanillic, p ‐coumaric and ferulic acids as bound acids and flavonols such as kaempferol and quercetin 3‐ O ‐apifuranosyl‐galactopyranoside, kaempferol and quercetin 3‐ O ‐dirhamnosyl‐galactopyranoside, quercetin glucuronide and others.…”
Section: Resultsmentioning
confidence: 99%
“…These two flavonols (peaks 7 and 14) have been also identified in different quinoa varieties by Gómez‐Caravaca et al . (, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Zhou et al (19) reported the presence of chemical constituents ( p -(acetylamino)phenol, ayamenin A, irisone, and salicin) of the water and ethyl acetate extracts of Agriophyllum squarrosum . Gómez-Caravaca et al (20) reported on the phenolic composition of Chenopodium species. Mirando et al (21) noted the presence of phenolics in quinoa seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the saponins and their known effects on various arthropods, the extract components of C. quinoa have not been identified and quantified, and their mode of action is unknown. The identification and quantification of saponins of C. quinoa have been studied in recent years (Woldemichael & Wink 2001;Zhu et al 2002;Kuljanabhagavad & Wink 2009;Gómez-Caravaca et al 2012). Lozano et al (2012) determined that the total amount of saponins in an ethanolic extract obtained from peel grain quinoa was in the range of 47.3 % to 56.0 %.…”
Section: Discussionmentioning
confidence: 99%